Total Productive Maintenance and Performance of Bottling Company Plants in Edo State. (International Journal of Scientific Research and Management (IJSRM), 2019)
The broad objective of this paper is to determine the effect of total productive maintenance on performance of selected bottling company plants in Edo State. Specifically, this paper seeks to ascertain the effect of planned maintenance on the competitive advantage of selected bottling company plants in Edo State. Survey research design was adopted for the study, a total population of two hundred and sixty nine (269) was used for the study, census sampling method was used for the study because the population is a manageable size, the data collection tool employed by the researcher was the questionnaire, while the analysis of the data was done using the linear regression analysis. The findings revealed that planned maintenance impacts the competitive advantage of selected bottling company plants in Edo State since (F = 223.041; R2 = 0.832; P <.05). The researchers therefore concluded that total productive maintenance impacts the performance of the companies in focus. It was against this backdrop that the researchers recommended that heads of the production department of the companies in focus should ensure the enactment of a schedule geared towards regularly maintaining their production equipments and an orientation of new employees on the importance of equipment maintenance should be done by heads of the production department of the companies in focus.